Species selection and plantation management in enrichment planting with native timber species in the Panama Canal watershed - Marshall, Abigail; Nelson, Cara R.; Hall, Jefferson S. (Frontiers in Forests and Global Change, 2022)
Large areas of the Panama Canal Watershed have been converted to monocultures of teak (Tectona grandis), a non-native timber species that is generally not providing hoped-for economic and ecological benefits of Forest Landscape Restoration. Enrichment planting offers a potential strategy for revitalizing these underperforming plantations through the addition of high-value, native species to the understory, but more information is needed to guide implementation and management in this region and other tropical areas. We assessed the performance of six promising native species (B. crassifolia, D. retusa, D. oleifera, H. alchorneoides, P. pinnatum, T. amazonia) as an enrichment planting in teak plantations, and specifically considered how light availability, crowding pressure and annual fertilization affected seedling performance, we measured survival and growth for the first 30 months post-planting for 3,000 seedlings; half received annual fertilization and half did not. We found that growth rate did not significantly affect survival among- or within-species, except for a positive relationship for D. oleifera. Overall seedling survival was high (83%), and, while species varied widely, there was not a strong effect of light, crowding or fertilization on survival. In contrast, overall growth of species was significantly affected by these factors. Across all species growth was negatively related to crowding and positively related to light availability and fertilization. There were among-species differences; while all but one species (D. oleifera) were negatively affected by crowding, only half responded positively to light availability (D. retusa, P. pinnatum, and B. crassifolia) and fertilization (D. retusa, P. pinnatum, and T. amazonia). Our findings suggest that all study species except for B. crassifolia, which suffered unacceptably high mortality, have high potential for use in enrichment planting in Panama teak plantations. Among-species differences in response to fertilization and growing environment highlight the need for continued studies to establish specific silvicultural guidelines for species in the enrichment planting context.